Manajemen MUI Tapanuli Utara Dalam Membina Umat Islam di Tengah Penduduk Minoritas Muslim di Tapanuli Utara - Sobirin Ramayanto Tampubolon; Waizul Qarni (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Living as one is the fantasy of all animals on the planet. However, religious people in the North Tapanuli Regency of North Sumatra, as well as other human beings, are subject to social conflict due to a variety of factors. In this manner, there should be a work to make agreement in the existence of strict individuals. The Indonesian Ulema Council of the North Tapanuli Regency in North Sumatra has worked to improve communication between the various religious communities in the North Tapanuli Regency in North Sumatra in order to foster a peaceful and harmonious religious environment. This is why the study titled "Leadership Management of North Tapanuli Mui in Fostering Muslims Among a Non-Muslim Majority Population" is deemed necessary. This kind of examination is field research (field research), while the idea of this exploration is distinct subjective, the information wellsprings of this examination are essential and auxiliary information. Primary data were gathered from daily administrators, members of the Commission for Religious Harmony, the Chairman of the Ukhuwah Islamiyah Commission, and members of the Commission for Interreligious Harmony. In the meantime, pertinent previous research results and journal books served as sources of secondary data. Interviews, observation, and documentation are all methods of data collection. Deductive thinking methods are utilized for the data analysis, which begins with generalizations before drawing more specific inferences. The study's findings demonstrate that the Indonesian Ulema Council of North Tapanuli Regency, North Sumatra's efforts to foster Muslims in North Tapanuli Regency, North Sumatra, including planning, organizing, monitoring, and evaluating aspects, have been successful. The inside improvement program for Muslims utilizes steps and strategies pointed toward making amicability among Muslims. Encouraging Muslims and non-Muslims by building social-strict relations, building social-instructive relations, building socio-political relations and building financial relations. Keywords: Management, Coaching, Muslim Ummah